Different metabolic activity in placental and reflected regions of the human amniotic membrane. Issue 11 (November 2015) - Banerjee, Asmita; Weidinger, Adelheid; Hofer, Martin; Steinborn, Ralf; Lindenmair, Andrea; Hennerbichler-Lugscheider, Simone; Eibl, Johann; Redl, Heinz; Kozlov, Andrey V.; Wolbank, Susanne
Abstract: Cells of the human amniotic membrane (hAM) have stem cell characteristics with low immunogenicity and anti-inflammatory properties. While hAM is an excellent source for tissue engineering, so far, its sub-regions have not been taken into account. We show that placental and reflected hAM differ distinctly in morphology and functional activity, as the placental region has significantly higher mitochondrial activity, however significantly less reactive oxygen species. Since mitochondria may participate in processes such as cell rescue, we speculate that amniotic sub-regions may have different potential for tissue regeneration, which may be crucial for clinical applications. Highlights: 4-fold higher mitochondrial activity in placental compared to reflected amnion. Identical quality of mitochondria in placental and reflected amnion. Similar mtDNA copy numbers per cell in placental and reflected amnion. Significantly higher levels of reactive oxygen species in reflected amnion.